Electroacupuncture Reduces Body Weight by Regulating Fat Browning-Related Proteins of Adipose Tissue in HFD-Induced Obese Mice - Lu, Sheng-Feng; Tang, Yue-Xia; Zhang, Tao; Fu, Shu-Ping; Hong, Hao; Cheng, Yu; Xu, Hou-Xi; Jing, Xing-Yue; Yu, Mei-Ling; Zhu, Bing-Mei (Frontiers in Psychiatry, 2019)
Objective: This study investigated the influence of electroacupuncture (EA) and its potential underlying mechanisms on adipose tissue in obese mice. Methods: Three-week-old male C56BL/6 mice were randomly divided to feed or not to feed high-fat diet (HFD), named HFD group and chow diet (CD) group, respectively. After 12 weeks, CD and HFD mice were randomly divided into two groups, respectively, to receive or not receive EA for 4 weeks. Body weight (BW) was monitored. Intraperitoneal glucose tolerance test and metabolic chamber recordings were performed. Blood samples and adipose tissue were collected for the analysis of leptin, triglyceride levels, and fat browning-related proteins. Results: EA significantly reduced food intake, BW, and white adipose tissue (WAT)/BW ratio; decreased the adipocyte size and serum concentrations of triglyceride (TG) and cholesterol; and increased oxygen consumption in HFD mice. Compared with the CD mice, the HFD mice had elevated fasting serum glucose level and impaired glucose tolerance; however, these parameters were decreased by EA treatment. Meanwhile, EA promoted the protein and mRNA expressions of UCP1, PRDM16, and PGC-1α in adipose tissue, and activated sympathetic nerves via p-TH, A2AR, and β3AR in white adipose tissue. Conclusions: EA reduced food intake, BW, TG, and cholesterol, and improved glucose tolerance in HFD mice. This ameliorative effect of EA on obesity-related symptoms associated with its promoted adipose tissue plasticity via activating sympathetic nerves.